Surya Majapahit’s Visual Transformation: From Hindu Temples to the Great Mosque of Demak - Wisnu Adisukma; Ranang Agung Sugihartono; Harmilyanti Sulistyani (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study traces the visual transformation of the Surya Majapahit, the eight-pointed solar emblem of Majapahit, as it moved from Hindu-Buddhist temples to the Islamic Great Mosque of Demak in Java. While prior scholarship has focused on the motif within its original religious context, how it was actively renegotiated during the Hindu-Islamic transition remains underexamined. Using Erwin Panofsky’s iconological method integrated with translocality, data were drawn from direct observation of six key artifacts spanning the Majapahit, transitional, and Demak periods, supplemented by interviews with site custodians. The analysis identifies a three-phase transformation: from a dense mandala containing anthropomorphic deities, through progressive figurative reduction, to a fully abstract geometric ornament integrated into Islamic decorative schemes. The radial core and central circle persistently survived, while narrative theological content was systematically eliminated. This process, termed “semiotic thinning,” involves the selection of a pliable structural core, reduction of specific iconography, and repositioning across mediums and spaces to align with aniconic Islamic aesthetics. The study concludes that this mechanism of visual negotiation enabled cultural continuity and the production of a new Javanese-Islamic identity. The findings contribute a model of symbolic adaptation in contexts of religious change.